2021
DOI: 10.2217/fon-2021-0618
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Use and Acceptance of Biosimilar Monoclonal Antibodies of Rituximab in Oncology Practice in the USA

Abstract: Aim: To describe treatment patterns and patient and provider characteristics associated with the recently introduced biosimilar rituximab-pvvr. Methods: This retrospective analysis included adult patients with one or more claims for rituximab-pvvr, with an index date of 23 January 2020 and a study period covering 1 January 2019–31 July 2020. Results: Of 249 patients included, the most common rituximab-pvvr indications were non-Hodgkin’s lymphoma (77.5%) and chronic lymphocytic leukemia (11.2%). Some patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(26 reference statements)
2
3
0
Order By: Relevance
“…The older the patients were, the higher the probability they would adopt biosimilars. This finding was consistent with the existing evidence ( Shelbaya et al, 2021 ; Yang et al, 2022 ). Elderly patients may be more price sensitive and tend to use cheaper biosimilars, hoping to avoid a heavier financial burden on themselves or their children.…”
Section: Discussionsupporting
confidence: 94%
“…The older the patients were, the higher the probability they would adopt biosimilars. This finding was consistent with the existing evidence ( Shelbaya et al, 2021 ; Yang et al, 2022 ). Elderly patients may be more price sensitive and tend to use cheaper biosimilars, hoping to avoid a heavier financial burden on themselves or their children.…”
Section: Discussionsupporting
confidence: 94%
“…The cost difference between two treatments and, hence, affordability might also have played a role in treatment selection. High number of Reditux™ prescriptions indicate global acceptance of biosimilar as observed in other published studies ( 12 , 23 , 27 ). A similar prescription pattern was noted in a real-world study conducted in Germany (2017–2019) where, within 2 years, the proportion of rituximab prescriptions for NHL/CLL for rituximab biosimilar increased from 12.0% to 83.0% against innovator rituximab with 90% of patients receiving a rituximab biosimilar by the end of the observation time ( 15 ).…”
Section: Discussionsupporting
confidence: 68%
“…First, unequal distribution of patients between cohorts and unequal distribution of certain baseline characteristics that necessitates us to rely on cautious evaluation and adjustment of baseline imbalances by the use of multivariate statistical method. Second, missing values that are expected in a real-world study as was observed in an earlier study ( 27 ) could lead to the possibility of not detecting some variables as relevant predictors of response. In addition, higher number of patient dropouts was observed during the course of the study.…”
Section: Implications and Limitationsmentioning
confidence: 91%
“…Improvements include extending the in-use stability to mitigate the impact of cold-chain rupture and exceptional temperature excursions on drug wastage and the quality of the product (Vieillard et al 2017 ; Park et al 2020 ). Even without the implementation of product optimizations, biosimilars are considered a customer-centric alternative to their branded counterparts solely based on the potential to increase access to mAb-based cancer medicines globally via reduced product costs compared to the originator mAb (Patel et al 2018 ; Shelbaya et al 2021 ). Here, interestingly, actual realization of a switch from branded to follow-on biologic or a switch from one to another biosimilar varies significantly from country to country.…”
Section: Key Developments In Providing Customer-centric Product Prese...mentioning
confidence: 99%